RENAL EXCRETION OF ZINC IN NORMAL INDIVIDUALS DURING ZINC TOLERANCE-TEST AND GLUCOSE-TOLERANCE TEST - Brandaoneto, J.; Shuhama, T.; Pimenta, W. P.; Piesco, R. V.; Castro, AVB; Mazeto, GMGS; Chung, J. S.; Franco, RJS; Curi, P. R. (Dustri-verlag Dr Karl Feistle, 1995)
The urinary excretion, renal clearance, and tubular reabsorption of zinc were investigated in 30 adult healthy subjects under basal conditions and during the zinc and glucose tolerance tests. After a 12h overnight fast, each subject was submitted to renal clearance of zinc. The procedures were performed between 8.00 and 12.00 a.m., after emptying the bladder and ingestion of 4 ml deionized water/kg body weight at 8.00 a.m. The first urine sample was collected at 10.00 a.m., and the second at 12.00 a.m. A dose of 110 mg ZnSO4.7H(2)O was administered orally to each subject, diluted in 20 mi deionized water, at time 0 min. Blood samples were collected from an antecubital vein at times -30, 0, and 30 min and at 30 min intervals up to 240 min. Glucose was administered intravenously (0.5 ml 50%/kg body weight) during the first 3 min of the test, and blood samples were collected from an unconstricted, contralateral, antecubital vein at times -30, 0, 3, 5, 10, 20, 30, 45, 60, and 90 min. The results showed that urinary zinc excretion, and renal zinc clearance were significantly higher during the zinc and glucose tolerance tests than in the control condition. on the other hand, renal zinc clearance was more elevated during the glucose tolerance test than during the zinc tolerance test. Variations in zinc tubular reabsorption and glomerular filtration rate were not detected. The results suggest that urinary excretion and renal clearance of zinc in healthy subjects increase during acute zinc ingestion and glucose infusion. Although zinc ingestion raised urinary zinc excretion, glucose infusion was more effective in increasing renal zinc clearance. These normal parameters are important in the investigation of diabetic patients with serum and urine zinc changes.
Keywords: ZINC TOLERANCE TEST; GLUCOSE TOLERANCE TEST; URINARY ZN EXCRETION; RENAL ZN CLEARANCE; C-ZN/C-CR RATIO; ZINC TUBULAR REABSORPTION; NORMAL INDIVIDUALS